Mechanism of a Novel Complex: Zinc Oxide Nanoparticles-Luteolin to Promote Ferroptosis in Human Acute Myeloid Leukemia Cells in Vitro - Wang W; Li Z; Lyu C; Wang T; Han C; Cui S; Wang J; Xu R (International Journal of Nanomedicine)
Wenhao Wang,1,* Zonghong Li,2,* Chunyi Lyu,1 Teng Wang,1 Chen Han,1 Siyuan Cui,3 Jinxin Wang,3 Ruirong Xu3– 5 1First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 2Department of Hematology, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, People’s Republic of China; 3Department of Hematology, Shandong University of Traditional Chinese Medicine Affiliated Hospital, Jinan, People’s Republic of China; 4Key Laboratory of Integrated Traditional Chinese and Western Medicine for Hematology, Health Commission of Shandong Province, Jinan, People’s Republic of China; 5Institute of Hematology, Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruirong Xu, Shandong University of Traditional Chinese Medicine Affiliated Hospital, Jinan, 250000, People’s Republic of China, Email shandongxuruirong@163.comPurpose: Acute myeloid leukemia (AML) is a hematological malignancy. Zinc oxide nanoparticles (ZnO NPs) and Luteolin are commonly used to fight cancer. In this study, we synthesized a new complex: zinc oxide nanoparticles-luteolin (ZnONPs-Lut) and aimed to investigate its effects on cell death in the AML cell line (MOLM-13) in vitro and to elucidate the underlying mechanisms.Methods: We assessed cell viability, quantified changes in gene expression using real-time quantitative PCR (qRT-PCR), and measured changes in ferrous (Fe2+) content, glutathione (GSH) content, malondialdehyde (MDA) content, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) levels following treatment with different concentrations of MOLM-13 cells with different concentrations of ZnONPs-Lut. Western blotting was used to detect the protein expression levels of ACSL4, GPX4, FTH1, and SLC7A11, while the cell morphology was observed by transmission electron microscopy (TEM). Meanwhile, the effect of Ferrostatin-1 (Fer-1), a ferroptosis inhibitor, on the expression of the aforementioned ferroptosis-related proteins and cell morphology was evaluated.Results: The results showed that ZnONPs-Lut was able to significantly inhibit the proliferation of MOLM-13 cells in a time- and dose-dependent manner. Additionally, it increased the concentrations of Fe2+ and MDA, reduced the expression levels of GSH and MMP, and induced ROS generation. Furthermore, it also enhanced the expression of ACSL4 protein while decreasing the expression of GPX4, FTH1, and SLC7A11 proteins. Notably, Fer-1 was able to significantly restrain the changes in protein levels and mitochondrial morphology damage induced by ZnONPs-Lut after its action on cells.Conclusion: ZnONPs-Lut inhibits the proliferation of MOLM-13 cells, likely through promoting the cellular ferroptosis signaling pathway. These findings suggest that ZnONPs-Lut could be a potential therapeutic approach for AML.Keywords: acute myeloid leukemia, ferroptosis, reactive oxygen species, zinc oxide nanoparticles, luteolin